Enhancing satiety and aerobic performance with beer microparticles-based non-alcoholic drinks: exploring dose and duration effects - Cahuê, Fábio Luiz Candido; Maia, Paola D. D. S.; de Brito, Luan Ribeiro; da Silva, Victor Paulo Ferreira; Gomes, Diego Viana; Pierucci, Anna Paola T. R. (Frontiers in Nutrition, 2024)
Beer is an alcoholic beverage, rich in carbohydrates, amino acids, vitamins and polyphenols, consumed worldwide as a social drink. There is a large number of beer styles which depends on the ingredients and brewing process. The consumption of beer as a fluid replacement after sport practice is a current discussion in literature. A non-alcoholic pale-ale microparticles-based beverage (PABM) have been previously designed, however, its phenolic profile and ergogenic effect remain unknown. Thus, this study aims to verify the ergogenic potential (increase of running performance) of PAMB in male Wistar rats. Beer microparticles were obtained by spray drying and beverages with different concentrations were prepared in water. Wistar rats were subjected to a training protocol on a treadmill (5 times/week, 60 min/day) and daily intake of PABM (20 mg.kg-1 or 200 mg.kg-1) or water by gavage. Chlorogenic acid was found to be the main component in the phenolic profile (12.28 mg•g-1) of PABM analyzed with high-performance liquid chromatography and mass spectrometry. An increase in the aerobic performance was observed after 4 weeks in the 20 mg.kg-1 group, but the same dose after 8 weeks and a higher dose (200 mg.kg-1) blunted this effect. A higher dose was also related to decrease in food intake.These data suggest that PABM can improve satiety and aerobic performance, but its effect depends on the dose and time of consumption.